PEMANFAATAN KULIT PISANG RAJA (Musa textilia) SEBAGAI BAHAN BAKU PEMBUATAN KERUPUK, DAYA TERIMA DAN KANDUNGAN ZAT GIZINYA - Richfa Yani; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Peel Plantains contain nutrients which are high enough especially vitamins and minerals so that can be used as food ingredients with processed into flour. Crackers are snacks which are favored by all age group. The research purpose know receptivity and nutrients from crackers with utilizing peel plantain flour. This research is experimental research in completely randomized design with increased peel plantain it 20%, 30% and 40%. Nutrients analyze in the Biochemical Laboratory of FMIPA USU and PPKS Laboratory, Medan. Receptivity test have been done on 30 college students FKM USU, Medan. Data which are collected to treated with manual and analyzed with descriptive analysis of percentage qualitative that is qualitative which are obtained from panelists to be into quantitative. And then to determining whether or not to different in crackers organoleptic then will be done test phase that are Bartlett test for population variances similarity test. ANOVAs test will be used when uniform variants. Duncan test looks to the organoleptic different on each treatment. The result Peel plantain flour that is 0,17gram. The result carbohydrate analysis per 100gram that are (40,10gram, 30,08gram and 36,14gram), fat per 100gram that are (27,15gram, 38,43gram, and 27,28gram), ash per 100gram that are (4,68gram, 4,8 gram and 5,64gram) and calcium per 100gram that are (0.05gram, 0,07gram, and 0,11gram). The organoleptic research result on aroma that are the more peel plantain flour then it is more disliked, the crackers flavor which are most liked that is A2 (30%:70%), the crackers texture which are disliked that is A1 (20%:80%). The increase to peel plantains don’t influence color it. It is suggested that the crackers be used as an alternative complementary food when eating. Other than that, it needs further research about the use food additive in order to make crackers more interesting, also it further research about the other nutritional on crackers. Key Word: Crackers, Snacks, Plantains